1988
DOI: 10.1111/j.1365-2621.1988.tb08955.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Selected Biochemical Components, In Vitro Protein Digestibility and Amino Acids in Two Bean Cultivars During Germination

Abstract: This study investigates changes in lectin and trypsin inhibitor activity, SDS-PAGE peptide pattern, in vitro protein digestibility and amino acid composition during germination of two dry bean cultivars. Lectin activity in navy beans was reduced. Significant amounts of trypsin inhibitor activity in both navy and pinto beans remained after germination for 6 days. Glycopeptides, with molecular mass ranging from 25,000 to 27,000 daltons, from partial proteolysis of the major storage proteins were resistant to a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…Using PAGE, several authors observed a reduction in the number of protein bands during the germination of different leguminous seeds as a result of enzymatic degradation [1,6,13]. GANESH KUMAR & VENKATARAMAN [13], using total seed proteins, observed on SDS-PAGE a progressive decrease in the subunit numbers of higher molecular weights and the appearance of smaller ones after 9 days of germination.…”
Section: -Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using PAGE, several authors observed a reduction in the number of protein bands during the germination of different leguminous seeds as a result of enzymatic degradation [1,6,13]. GANESH KUMAR & VENKATARAMAN [13], using total seed proteins, observed on SDS-PAGE a progressive decrease in the subunit numbers of higher molecular weights and the appearance of smaller ones after 9 days of germination.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Protein characteristics and its mobilization during seed germination have been extensively studied in some species [1,4,6,11,25,29], indicating a slow hydrolysis, whose mechanism of degradation control is still uncertain. In addition, germination induces changes in protein [22,23] and starch digestibility, which probably also result from enzymatic action.…”
Section: Effect Of Chickpea (Cicer Arietinum L) Germination On the Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of which, soaking and germination has been acknowledged as a cost-effective technology and as it causes considerable changes in the nutritional and sensory characteristics of legumes [Vidal-Valverde et al 2002, Chang and Harrold 1988, Martín-Cabrejas et al 2008] which may be due to "breakdown of complex macromolecular structures of starch and proteins into reducing sugars and amino acids as a result of increased metabolic activity" as described by Mwikya et al [2001]. Hence, sprouted legumes either by themselves or combined with cereal fl ours, can produce highly nutritious and digestible foods [Prodanov et al 1997].…”
mentioning
confidence: 99%